Vapor-liquid equilibria of the binary systems nitrogen plus bromotrifluoromethane, plus bromochlorodifluoromethane, plus 1,1,1,2,3,3,3-heptafluoropropane, and plus trifluoroidomethane from 293.2 to 313.2 K and 30 to 100 bar - Lim, JS; Kim, JD (AMER CHEMICAL SOC, 1997)
Isothermal vapor-liquid equilibria were measured in the binary systems nitrogen + bromotrifluoromethane, nitrogen + bromochlorodifluoromethane, nitrogen + 1,1,1,2,3,3,3-heptafluoropropane, and nitrogen + trifluoroiodomethane in a circulation-type equilibrium apparatus. The temperature range was (293.2 to 313.2) K and the pressure range was (30 to 100) bar. The experimental data were well correlated with the Peng-Robinson equation of state using the Wong and Sandler mixing rule, and the relevant parameters are presented.
Keywords: MIXING RULE; STATE; EQUATION